The Student Empathy for a Prospective School Counselor : How Does Group Counseling Affect It? (An Analysis Based on Gender) - Nuraeni, Nuraeni; Suranata, Kadek (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the effect of group counseling on increasing the empathy of prospective counselor students. The research method uses Â an experimental one-group pretest-posttest control design. The subjects in this study were guidance and counselling students at the Mandalika University of Education, and classified as having low empathy criteria. Data collection was carried out using an empathy questionnaire. Data analysis used the one-way ANOVA statistical test. The results of this study indicate that group counselling affects increasing the empathy of guidance and counselling students at the Mandalika University of Education. Besides Â there are differences in the level of empathy between male and female students, where female students have higher empathy than male students.